Ti\(O_2\) Nanoparticles Acid-assisted Synthesis and the Enhanced Visible-light Photocatalytic Activity - Gu , Yi-Jie; Zhou, Ming; Dong, Zhihua; Cheng, Zhiqun; Deng , Tian-Song (Fundamental Research and Application of Physical Science Vol. 6, 2023)
The simple synthesis of TiO2 and improved visible-light photocatalytic performance of TiO2 have been the goal of researchers. When compared to pure phase TiO2, mixed-phase TiO2 nanoparticles with oxygen vacancies can aid in lowering the band gap and carrier recombination rate, which improves the performance of visible light photocatalysis. In this study, three different acids were separately applied in the hydrothermal synthesis of TiO2 nanoparticles without any post-heat treatment. The reaction was carried out at a relatively low temperature not exceeding \(140^{°}\)C. Under the visible light illumination-assisted photocatalytic degradation of methyl orange in water, the TiO2 nanoparticles obtained from HCl (H-TiO2) and CH3COOH (A-TiO2) showed stable photocatalysis performance for increasing the cycles up to ten times while only five cycles for TiO2 nanoparticles obtained by HNO3-assisted (N-TiO2). Compared with efficiencies of N-TiO2 nanoparticles, H-TiO2 and A-TiO2 showed superior efficiencies and have excellent photocatalytic performances when assisting in the degradation of methyl orange in water under visible light illumination. The high visible-light photocatalytic performance and the simple acid-assisted synthesis of the H-TiO2 and A-TiO2 nanoparticles will promote the industrial application.